SPATIAL ANALYSIS OF VACCINE COVERAGE FOR CHILDREN UNDER ONE YEAR OF AGE IN PERNAMBUCO - da Costa, Clara Ilda Oliveira; de Mello Antunes, Fernanda Maria Bezerra (Cadernos ESP, 2024)
To analyze vaccination coverage in children under one year of age in the state of Pernambuco. This is an ecological, quantitative study that analyzes and manages spatial/temporal data on vaccination coverage of three immunizers in children under one year of age in the state of Pernambuco. The temporal panorama of childhood vaccination in the state between 2012 and 2021, indicates that sharp drops in vaccination were recorded for the three immunizers (BCG, Poliomyelitis and Human Rotavirus). The reintroduction of eradicated diseases (measles and polio), as well as the Covid-19 pandemic, have accentuated the drops in childhood VC in Brazil, recorded since 2015. In this sense, it is essential for the SUS to promote equitable access for the population to primary health services. In other words, despite their success, vaccines do not dispense with the continuity of other health actions, especially prevention and promotion measures carried out in Primary Care.